Groundwater Exploration in Parts of Oyo and Ondo States Using Remote Sensing Techniques. - Adeyemi, Gabriel Oladapo (Obafemi Awolowo University, 2014)
Subsurface water in the basement complex areas is confined to the weathered overburden and the underlying fracture zones. The weathered overburden is only promising where it is thick and fairly sandy. These conditions are not obtained everywhere in the basement complex area. A large amount of groundwater is known to occur within fracture zones in the absence of thick overburden.